Near-infrared light-controlled carbon nanotube-enzyme-loaded hydrogel composite material and application thereof in enzyme-based electrochemical biosensing technology
By combining temperature-responsive hydrogel with carbon nanotubes, a near-infrared light-controlled carbon nanotube-enzyme-carrying hydrogel composite was prepared, which solved the problems of poor controllability of enzymes and difficulty in direct electron transfer in living analysis, and achieved reversible regulation of enzyme catalytic activity and improved electrochemical response.
Patent Information
- Application Number
- CN202510041489.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-10
AI Technical Summary
In live analysis, the poor controllability of enzymes and difficulty in direct electron transfer limit the application of enzyme-based electrochemical biosensors.
A temperature-responsive hydrogel combined with carbon nanotubes was used to prepare a near-infrared light-controlled carbon nanotube-enzyme-carrying hydrogel composite material. The morphology of the hydrogel is regulated through temperature or light to dynamically regulate the catalytic activity of the enzyme.
It realizes reversible regulation of enzyme catalytic activity, improves electrochemical response, is suitable for controllable analysis of living organisms, and has important biological application value.
Smart Images

Figure CN119751749A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biological detection, and specifically relates to a temperature-responsive hydrogel, an enzyme-loaded hydrogel and a carbon nanotube-enzyme-loaded hydrogel composite material prepared thereby, and applications of the temperature-responsive hydrogel in preparing enzyme-based electrochemical biosensors. Background Art
[0002] The nervous system contains a variety of chemicals, and the imbalance of these neurochemicals can cause behavioral disorders and neurological diseases. Therefore, studying neurochemical molecules is extremely important for understanding their role in brain function and major neurological diseases.
[0003] The analysis of brain neurochemical substances is generally divided into different levels such as single vesicle, single cell, brain slice and living body. Among them, the detection of chemical substances at the level of single vesicle, single cell and brain slice is out of the real environment of living body, and it is difficult to maintain the inherent connection and interaction between cells. In comparison, the analysis of brain chemical substances at the living body level can more truly and directly reflect the response of the nervous system to external stimuli in various physiological and pathological processes. The in vivo electrochemical analysis method uses microelectrodes implanted in specific brain regions to monitor the dynamic changes of neurochemical substances in the brain in situ. Because of its advantages such as high spatiotemporal resolution, real-time and in vivo, it has attracted much attention in neurochemical research. In recent years, enzyme-based electrochemical biosensors have been widely used. However, there are still the following two challenges in in vivo analysis. (1) Poor controllability of enzymes: Enzymes have high specificity and high efficiency catalysis for specific substrates, but biological enzymes have problems such as poor stability and difficult to control catalytic activity. (2) Difficult direct electron transfer: Direct electron transfer of biological enzymes on the electrode surface is the basis of bioelectrochemical devices. Direct electron transfer of enzymes on the electrode surface refers to the fact that the catalytic active center of the redox enzyme (which involves electrons in the catalytic process) can directly establish an electronic connection with the solid electrode surface, which is achieved by electron tunneling. Therefore, the active center of the enzyme needs to be close enough to the electrode surface, generally less than 2nm. However, the redox centers of most biological enzymes are deeply buried inside the molecules, so it is difficult to achieve direct electron transfer on the electrode surface.
[0004] Hydrogels are hydrophilic polymers with a three-dimensional network structure. They have soft properties similar to living tissues, which makes them ideal biomaterials. As a type of smart material, stimuli-responsive hydrogels not only have the advantages of traditional hydrogels, but also can sense small external stimuli (temperature, pH value, magnetic field strength, etc.), and their physical / chemical properties (such as volume, wettability, surface charge) can change dynamically. Among various smart hydrogels, PNIPAAm, as a typical temperature-responsive hydrogel, has been favored by many researchers. When the temperature changes near its lower critical solution temperature (LCST), the hydrogel morphology undergoes reversible swelling-contraction changes. Poly(N-isopropylacrylamide) (PNIPAAm) is temperature-responsive and undergoes phase change when the temperature changes. It can be used in drug carriers, tissue engineering, bioimaging and other fields. However, the LCST of PNIPAAm is 32°C, which is lower than the physiological temperature (37°C), which limits its application in the field of biotechnology.
[0005] In recent years, smart biocatalysts produced by combining enzymes with stimulus-responsive groups have received widespread attention. Depending on the presence or absence of external stimuli, the stimulus-responsive groups attached to the enzymes regulate the activity of the enzymes by changing conformation or other properties, thereby acting as molecular switches. At present, temperature-responsive smart enzymes have been reported. Palai (Palai T, Kumar A, Bhattacharya P K. Synthesis and characterization of thermo-responsive poly-N-isopropylacrylamide bioconjugates for application in the formation of galacto-oligosaccharides [J]. Enzyme Microb Technol, 2014, 55: 40-49.) conjugated PNIPAAm with β-galactosidase. The LCST of the bioconjugate was 26.5°C. After 24 precipitation-dissolution cycles, the enzyme activity was still maintained at about 90%. Although the reversible conformational changes of thermosensitive copolymers can be used to achieve the "on-off" effect of enzyme activity, in practical applications, especially in complex biological systems, it is impossible to directly use the heat source as an external control element to control the performance of the material by direct heating.
[0006] The regulation mode of light-regulated smart enzymes has the advantages of non-invasiveness, spatiotemporal specificity and non-pollution. Shimoboji et al. (Shimoboji T, Larenas E, Fowler T, et al. Photoresponsive polymer-enzyme switches [J]. Proc Natl Acad Sci USA, 2002, 99 (26): 16592-16596.) synthesized two photosensitive polymers by polymerizing N, N-dimethylacrylamide with 4-phenylazobenzene acrylate and N-4-phenylazobenzene acrylamide, and connected them with glucanase. Under specific light, the aggregation state of the polymer changes, and the purpose of controlling the enzyme activity is achieved by adjusting the contact between the enzyme active center and the substrate. However, most of the current light-regulated smart enzymes are constructed by combining azobenzene analogs, spiropyran groups or photosensitive protein domains with enzymes, and usually require high-energy lasers such as ultraviolet light or blue light to control the photosensitive groups. The preparation process is complicated, the cost is high, and it is difficult to achieve the degree of control of the switch. In addition, ultraviolet light or blue light has low biosafety and poor tissue penetration, making it unsuitable for analysis in living animals. Summary of the invention
[0007] In view of the shortcomings of the existing technology, the present invention provides a temperature-responsive enzyme-loaded hydrogel, and combines it with the concept of light regulation to further provide a near-infrared light-controlled carbon nanotube-enzyme-loaded hydrogel composite material, which is a new intelligent sensing technology suitable for controllable analysis of living bodies.
[0008] In order to achieve the purpose of the present invention, the specific technical solution of the present invention is as follows:
[0009] A temperature-responsive hydrogel is formed by a polymerization reaction of copolymer monomers: N-isopropylacrylamide, 1-pyrene methylacrylate and acrylic acid, and a crosslinking agent initiated by a free radical initiator.
[0010] Preferably, the molar ratio of N-isopropylacrylamide, 1-pyrene methacrylate and acrylic acid is 13-16:1-4:1-4.
[0011] In a specific example of the present invention, the molar ratio of N-isopropylacrylamide, 1-pyrene methacrylate and acrylic acid is 15:2:2.
[0012] Preferably, the cross-linking agent is selected from one or more of N,N-methylenebisacrylamide, ethylene glycol dimethacrylate, and polyethylene glycol diacrylate.
[0013] In a specific example of the present invention, the cross-linking agent is selected from N,N-methylenebisacrylamide.
[0014] Preferably, the free radical initiator is selected from one or more of ammonium persulfate, potassium persulfate, and azobisisobutyronitrile.
[0015] Preferably, the molar ratio of the comonomer, the crosslinking agent and the free radical initiator is 19:0.75:0.45.
[0016] In a specific example of the present invention, the temperature-responsive hydrogel is prepared by the following method: N-isopropylacrylamide, 1-pyrene methyl acrylate and acrylic acid are dissolved in water, N,N-methylenebisacrylamide and sodium dodecyl sulfate are added in sequence, the mixed solution is heated under a nitrogen environment, ammonium persulfate is added to initiate a polymerization reaction, the reaction is cooled to room temperature after the reaction is completed, and unreacted monomers are removed by dialysis to obtain a hydrogel.
[0017] Another object of the present invention is to provide an enzyme-loaded hydrogel, wherein the temperature-responsive hydrogel of the present invention is loaded with biological enzymes by one or more of physical adsorption, chemical cross-linking, and covalent bonding.
[0018] The enzyme-loaded hydrogel of the present invention can load any type of biological enzyme involved in the art, such as glucose oxidase and horseradish peroxidase.
[0019] Preferably, a cross-linking agent can be used to connect the bioenzyme molecules to the temperature-responsive hydrogel. The cross-linking agent is selected from 1-ethyl-(3-dimethylaminopropyl)carbodiimide and / or N-hydroxysuccinimide.
[0020] In the enzyme-loaded hydrogel of the present invention, the mass ratio of the biological enzyme to the temperature-responsive hydrogel is 0.2 to 1.4: 1. In a specific example of the present invention, the mass ratio of the biological enzyme to the temperature-responsive hydrogel is 1:1.
[0021] In a specific example of the present invention, the temperature-responsive hydrogel is suspended in a buffer solution containing 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC), and the EDC-activated hydrogel is mixed with a biological enzyme (such as glucose oxidase) at 4°C to react to prepare an enzyme-loaded hydrogel.
[0022] Another object of the present invention is to provide a carbon nanotube-enzyme-loaded hydrogel composite material, wherein the enzyme-loaded hydrogel of the present invention is doped with carbon nanotubes.
[0023] Preferably, the carbon nanotubes are multi-walled carbon nanotubes.
[0024] Preferably, the mass ratio of carbon nanotubes to enzyme-loaded hydrogel is 0.6-4.2:4, preferably 3:4.
[0025] Another object of the present invention is to provide an application of the temperature-responsive hydrogel, enzyme-loaded hydrogel or carbon nanotube-enzyme-loaded hydrogel composite material described in the present invention in the preparation of enzyme-based electrochemical biosensors.
[0026] The temperature-responsive hydrogel of the present invention has a lower critical solution temperature higher than the physiological temperature of 37° C., and can undergo reversible swelling-contraction changes regulated by temperature or light to dynamically regulate the catalytic activity of biological enzymes.
[0027] In a specific example of the present invention, the carbon nanotube-enzyme-loaded hydrogel undergoes reversible swelling-contraction changes under the control of near-infrared light to dynamically control the catalytic activity of the biological enzyme.
[0028] In the application of the present invention, the carbon nanotube-enzyme hydrogel is exposed to near-infrared light with an excitation light wavelength of 700-1700nm and a power of 0.2-2.0W / cm 2 , illumination time 0.1-5min. Preferably 1-4min. In a specific example of the present invention, the excitation light source is 1064nm, the power is 1W / cm 2 , illumination time 1 to 2 minutes.
[0029] Another object of the present invention is to provide a near-infrared light-controlled enzyme-based electrochemical biosensor, wherein the surface of the carbon electrode of the biosensor is coated with the enzyme-loaded hydrogel or carbon nanotube-enzyme-loaded hydrogel composite material described in the present invention.
[0030] Advantages of the present invention:
[0031] 1. The present invention selects N-isopropylacrylamide, 1-pyrene methacrylate and acrylic acid as comonomers by screening and adjusting the types and proportions of comonomers. The lower critical solution temperature of the prepared temperature-responsive hydrogel is higher than the physiological temperature of 37°C, so that it can be affected by temperature changes under physiological conditions to achieve dynamic regulation of enzyme catalytic activity.
[0032] 2. After multiple heating-cooling cycles, the light transmittance of the temperature-responsive hydrogel of the present invention remains basically unchanged, and the microgel has excellent temperature responsiveness and reversible phase transition ability.
[0033] 3. The temperature-responsive hydrogel structure of the present invention can protect the biological activity of the loaded biological enzyme.
[0034] 4. The present invention doped the enzyme-loaded hydrogel with multi-walled carbon nanotubes to prepare a carbon nanotube-enzyme-loaded hydrogel composite material. Based on the excellent light-to-heat conversion efficiency of carbon nanotubes, the composite material can convert near-infrared light energy into heat energy, thereby regulating the microgel morphology and further controlling the enzyme catalytic activity. Electrochemical studies have shown that the reversible regulation of the enzyme catalytic activity on the electrode surface can be achieved by using the above composite material to modify the carbon fiber electrode as the research object and near-infrared light as the external control element.
[0035] 5. The present invention utilizes the excellent electrical conductivity of carbon nanotubes. The change in microgel morphology promotes electron transfer in the three-dimensional conductive framework of the composite material, thereby improving the electrochemical response.
[0036] 6. The present invention selects 1-pyrene methacrylate as the comonomer of the hydrogel. The 1-pyrene methacrylate unit easily forms a π-π conjugated system with the carbon nanotubes, thereby promoting the stable modification of the material on the surface of the carbon electrode.
[0037] 7. The electrochemical research results of the present invention show that after multiple on-off cycles of near-infrared light, the oxidation peak current remains basically unchanged. This indicates that near-infrared light can be used to control enzyme catalytic reactions on the electrode surface. On this basis, using near-infrared light as a control element, a new intelligent sensing technology suitable for controllable analysis of living bodies can be constructed to promote clinical diagnosis and treatment, which has important biological application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 .Infrared spectrum (A) and nuclear magnetic resonance hydrogen spectrum (B) of temperature-responsive hydrogel PNI-co-AA-co-Py.
[0039] Figure 2 .(A) The transmittance of the temperature-responsive hydrogel PNI-co-AA-co-Py changes with temperature and (B) the cycle diagram of the hydrogel transmittance under temperature control of 25℃ and 55℃.
[0040] Figure 3 .Thermal stability of free enzyme and the enzyme-loaded hydrogel GOD@PNI-co-AA-co-Py described in the present invention at 45°C.
[0041] Figure 4 . Carbon nanotube-enzyme hydrogel composites (GOD@PNI-co-AA-co-Py / MWCNTs) with different multi-walled carbon nanotube doping amounts and pure water were exposed to near-infrared light (1064 nm, 1.0 W / cm 2 ) Temperature changes under irradiation.
[0042] Figure 5.Scanning electron micrographs of multi-walled carbon nanotube carbon fiber electrode (A), enzyme-loaded hydrogel carbon fiber electrode (B) and carbon nanotube-enzyme-loaded hydrogel carbon fiber electrode (C).
[0043] Figure 6 . Carbon nanotube-enzyme-loaded hydrogel composite (GOD@PNI-co-AA-co-Py / MWCNTs) modified electrode controls the catalytic activity of glucose oxidase. (A) Cyclic voltammogram of composite modified electrode before and after near-infrared irradiation; (B) On-off cycle of oxidation peak current under near-infrared light control.
[0044] Figure 7 .Effect of multi-walled carbon nanotube doping amount on the catalytic activity of glucose oxidase controlled by carbon nanotube-enzyme-loaded hydrogel composite (GOD@PNI-co-AA-co-Py / MWCNTs) modified electrode.
[0045] Figure 8 .Effect of enzyme loading amount on the catalytic activity of glucose oxidase controlled by carbon nanotube-enzyme-loaded hydrogel composite (GOD@PNI-co-AA-co-Py / MWCNTs) modified electrode.
[0046] Fig. 9 . Carbon nanotube-enzyme hydrogel composite (GOD-HRP@PNI-co-AA-co-Py / MWCNTs) modified electrode controls the catalytic activity of glucose oxidase-horseradish peroxidase cascade reaction. (A) Electrochemical response of the modified electrode to glucose molecules before and after near-infrared light irradiation. (B) Electrochemical response of different concentrations of glucose on the composite modified electrode under near-infrared light irradiation.
[0047] Fig.10 .Electrochemical response of the catalytic activity of glucose oxidase-horseradish peroxidase cascade reaction to glucose molecules in the mouse brain controlled by the carbon nanotube-enzyme loaded hydrogel composite (GOD-HRP@PNI-co-AA-co-Py / MWCNTs) modified electrode before and after near-infrared light irradiation. DETAILED DESCRIPTION
[0048] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments, but the embodiments cannot be understood as any limitation to the present invention. The protection scope of the present invention is subject to the claims. Unless otherwise specified, the following embodiments are all completed using conventional existing technologies.
[0049] Example 1 Preparation of temperature-responsive hydrogel PNI-co-AA-co-Py
[0050] 0.170 g N-isopropylacrylamide (NIPAAm), 0.063 g 1-pyrene methacrylate (Py-Ac) and 0.014 g acrylic acid (AA) were dissolved in 95 mL deionized water. 0.012 g N,N-methylenebisacrylamide (MBAA) and 0.0017 g sodium dodecyl sulfate (SDS) were added in sequence under stirring. The mixed solution was heated to 70 °C under nitrogen atmosphere, and then ammonium persulfate (APS) (0.01 g dissolved in 5 mL) was added to initiate the polymerization reaction (the concentration of N-isopropylacrylamide in the reaction system was 15 mM, the concentration of 1-pyrene methacrylate was 2 mM, and the concentration of acrylic acid was 2 mM). After reacting for 7 hours, the reaction solution was cooled to room temperature and then dialyzed for 7 days to prepare PNI-co-AA-co-Py hydrogel.
[0051] Performance characterization:
[0052] 1. Composition and structural characterization of PNI-co-AA-co-Py hydrogel
[0053] Infrared spectrum ( Figure 1 A) and H NMR spectra ( Figure 1 B) All show that the PNI-co-AA-co-Py hydrogel contains three monomers, confirming the successful polymerization of the monomers.
[0054] 2. Study on the temperature response properties of PNI-co-AA-co-Py hydrogel
[0055] Take 0.1% hydrogel in a cuvette and use a UV-visible spectrophotometer to measure the transmittance of the sample at different temperatures. The temperature range is 25-55°C. Keep the sample stable at the reading temperature for 10 minutes before each reading. Draw the temperature-transmittance change curve of the hydrogel based on the results ( Figure 2 A).
[0056] Experimental data show that the phase transition temperature of the gel is 39°C, which is greater than the physiological temperature (37°C). In order to verify the repeatability of PNI-co-AA-co-Py hydrogel to temperature, the change in transmittance of PNI-co-AA-co-Py after 5 cycles at 25°C and 55°C was detected. The results are shown in Figure 2. Figure 2 As shown in Figure B, after multiple heating-cooling cycles, the transmittance of the hydrogel remains basically unchanged. The above data show that the hydrogel has excellent temperature responsiveness and reversible phase transition ability.
[0057] Example 2 Effect of comonomer ratio on temperature response properties of hydrogel
[0058] Hydrogels with different comonomer molar ratios were prepared by referring to the preparation method of Example 1, and the influence on the temperature response performance of the hydrogels was investigated.
[0059] The results are shown in Table 1. The results show that with the increase of acrylic acid, the lower critical solution temperature of the hydrogel gradually increases. When the molar ratio of N-isopropylacrylamide, acrylic acid, and 1-pyrene methacrylate is 13-16:2:1-4, the lower critical solution temperature of the PNI-co-AA-co-Py hydrogel is close to the physiological body temperature of the human body of 36.0-37.0°C. The hydrogel prepared by preferably having a molar ratio of N-isopropylacrylamide, acrylic acid, and 1-pyrene methacrylate of 15:2:2 has a lower critical solution temperature of 39°C, which is more suitable for in vivo application analysis.
[0060] Table 1
[0061]
[0062] Example 3 Preparation of enzyme-loaded hydrogel GOD@PNI-co-AA-co-Py
[0063] The PNI-co-AA-co-Py hydrogel (2 mg) prepared in Example 1 was suspended in a buffer (5 mL) containing 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC, 4 mg). The EDC-activated hydrogel was mixed with glucose oxidase (GOD, 2 mg) and reacted for 10 hours at 4°C. After the reaction, the hydrogel was purified to prepare an enzyme-loaded hydrogel (GOD@PNI-co-AA-co-Py).
[0064] Performance characterization: Investigating the thermal stability of enzymes in enzyme-loaded hydrogels.
[0065] The hydrogel solution (GOD@PNI-co-AA-co-Py) immobilized with glucose oxidase (GOD) was incubated at 45°C for 150 min with the free glucose oxidase (GOD) solution, and a portion of the sample was taken out every 30 min for activity determination. The biological activity of GOD was evaluated based on the HRP-H2O2-TMB enzymatic reaction. The concentrations of GOD and free GOD in the enzyme-loaded hydrogel were kept consistent (e.g., 20 μg / mL). Free GOD or enzyme-loaded hydrogel was dispersed in 0.1 mL Tris buffer (pH 7.5, 50 mM) containing 10 μg / mL horseradish peroxidase (HRP), and then 0.2 mL of the prepared TMB solution was added as a hydrogen donor. Glucose solution (5 mM, 0.2 mL) was immediately added to activate the catalytic reaction. The generated H2O2 can oxidize TMB, and the absorbance at 650 nm was recorded by a UV-visible spectrophotometer.
[0066] The results are as follows Figure 3As shown, compared with naked enzyme, the enzyme activity loss of the enzyme-loaded hydrogel (GOD@PNI-co-AA-co-Py) of the present invention is less, which proves that the hydrogel structure can protect the enzyme activity.
[0067] Example 4 Preparation of carbon nanotube-enzyme-loaded hydrogel composite material (GOD@PNI-co-AA-co-Py / MWCNTs)
[0068] The enzyme loaded hydrogel (GOD@PNI-co-AA-co-Py) prepared in Example 3 was mixed with different amounts of multi-walled carbon nanotubes (MWCNTs), wherein the concentration of the enzyme loaded hydrogel (GOD@PNI-co-AA-co-Py) was 2 mg / mL, and the concentrations of the multi-walled carbon nanotubes were 1.5 mg / mL, 0.8 mg / mL, 0.4 mg / mL, and 0.2 mg / mL, respectively. The mixture was thoroughly mixed by ultrasonication in an ice-water bath for 30 min, and carbon nanotube-enzyme loaded hydrogel composites (GOD@PNI-co-AA-co-Py / MWCNTs) with different carbon nanotube contents were prepared through π-π interaction self-assembly.
[0069] Example 5 investigates the photothermal conversion effect of the carbon nanotube-enzyme-loaded hydrogel composite material.
[0070] The composite material solution prepared in Example 4 was irradiated with near infrared light. This experiment used a 1064 nm laser with a power of 1 W / cm 2 , illumination time 4min, ultrapure water was used as blank control group, and the temperature changes of different composite material solutions were measured under the same conditions.
[0071] The results are as follows Figure 4 As shown in the figure, the temperature of the carbon nanotube-enzyme hydrogel composite (GOD@PNI-co-AA-co-Py / MWCNTs) solution gradually increases with the increase of illumination time. In addition, as the content of MWCNTs in the composite increases, the heating rate is faster. However, under the same experimental conditions, the temperature of pure water has hardly changed. The above results show that MWCNTs in the composite can effectively absorb near-infrared light and generate enough heat. When the solution temperature is lower than the critical temperature, the gel is in a swollen state; when the solution temperature is higher than the critical temperature, the gel is in a contracted state. Based on this, the properties of the composite material can be regulated by near-infrared light, and the catalytic activity of the enzyme can be further regulated.
[0072] Example 6: Using electrochemical technology to explore the reversible regulation of enzyme catalytic activity in composite materials
[0073] Preparation of composite material modified electrodes: Drop the composite material solution (0.5 mL) with a mass ratio of 4:3 of enzyme-loaded hydrogel to multi-walled carbon nanotubes prepared in Example 4, the enzyme-loaded hydrogel solution (2 mg / mL, 0.5 mL) prepared in Example 3, and the multi-walled carbon nanotube solution (1.5 mg / mL, 0.5 mL) on a flat glass. Under a microscope, immerse the carbon fiber electrode (length: 1 mm, diameter: 8 μm) in the droplets and rotate repeatedly. Then dry them to prepare composite material functionalized carbon fiber electrodes, multi-walled carbon nanotube carbon fiber electrodes, and enzyme-loaded hydrogel carbon fiber electrodes. The scanning electron microscope images of the three electrodes are shown in the figure below. Figure 5 As shown, the surface of the multi-walled carbon nanotube carbon fiber electrode is coated with multi-walled carbon nanotube fibers and has a smooth surface; the surface of the enzyme-loaded hydrogel carbon fiber electrode presents hydrogel microspheres; and the carbon nanotubes on the surface of the composite material functionalized carbon fiber electrode are well embedded in the enzyme-loaded hydrogel microspheres.
[0074] This example uses electrochemical technology to further study the reversible regulation of enzyme catalytic activity by near-infrared light. The electrochemical test uses a three-electrode system, in which a composite material functionalized carbon fiber electrode is used as a working electrode, a platinum wire is used as a counter electrode, and a silver / silver chloride electrode is used as a reference electrode. A 1064nm laser is used as a light source. In the electrochemical measurement, the electrolyte solution is artificial cerebrospinal fluid (pH = 7.4). The working electrode, counter electrode, and reference electrode are inserted into the artificial cerebrospinal fluid, and high-purity nitrogen is ventilated. The scanning potential range of the cyclic voltammogram is -0.7 to 0.4V, and the scanning rate is 50mV / s. Figure 6 As shown in A, when there is no near-infrared light irradiation, the composite modified electrode does not produce obvious peak current. However, near-infrared light (1064nm, 1.0W / cm 2 ) for 2 minutes, the current increased, and a pair of obvious redox peaks were obtained on the electrode surface, proving that glucose oxidase in the composite material can achieve direct electron transfer on the electrode surface. This is because under near-infrared light irradiation, the hydrogel changes from a swollen state to a contracted state, thereby promoting the active site of glucose oxidase to approach the electrode surface. In addition, carbon nanotubes have excellent conductivity, and the change in the morphology of the hydrogel promotes electron transfer in the three-dimensional conductive framework of the composite material, thereby improving the electrochemical response. Figure 6 As shown in B, after multiple on-off cycles of near-infrared light, the oxidation peak current remains basically unchanged. The above results indicate that near-infrared light can be used to control enzyme-catalyzed reactions on the electrode surface.
[0075] Example 7 Effect of comonomer 1-pyrene methacrylate (Py-Ac) on the enzyme catalytic activity of carbon nanotube-enzyme-loaded hydrogel composites
[0076] The Py-Ac unit in the gel PNI-co-AA-co-Py of the present invention has a conjugated aromatic ring structure and is easy to form a π-π conjugated system with MWCNTs, thereby helping the material to be stably modified on the surface of the carbon electrode, promoting direct electron transfer between the enzyme and the electrode, and further improving the electrochemical response signal.
[0077] Based on this, referring to the methods of Examples 3, 4, and 6, carbon nanotube-enzyme-loaded hydrogel composites with different Py-Ac molar ratios were prepared (the mass ratio of hydrogel to glucose oxidase was 1:1, and the mass ratio of enzyme-loaded hydrogel to multi-walled carbon nanotubes was 4:3) and corresponding carbon fiber electrodes were prepared to investigate the effect on the enzyme catalytic activity of the carbon nanotube-enzyme-loaded hydrogel composites.
[0078] The results are shown in Table 2, which show that as the proportion of 1-pyrene methacrylate increases, the oxidation peak current increases; when the molar ratio of N-isopropylacrylamide, acrylic acid, and 1-pyrene methacrylate is 15:2:2, the oxidation peak current reaches a maximum value and then gradually decreases. Preferably, the molar ratio of N-isopropylacrylamide, acrylic acid, and 1-pyrene methacrylate is 15:2:2.
[0079] Table 2
[0080]
[0081] Example 8 Effect of Multi-walled Carbon Nanotube Content on Catalytic Activity
[0082] The molar ratio of N-isopropylacrylamide, acrylic acid, and 1-pyrene methylacrylate was 15:2:2, and the mass ratio of hydrogel to glucose oxidase was 1:1. The enzyme-carrying hydrogel was further mixed with different amounts of multi-walled carbon nanotubes (MWCNTs), and the multi-walled carbon nanotube content in the solution was 0.3 mg / mL, 0.6 mg / mL, 0.9 mg / mL, 1.2 mg / mL, 1.5 mg / mL, 1.8 mg / mL, 2.1 mg / mL, and ultrasonicated in an ice-water bath for 30 min to obtain a carbon nanotube-carrying enzyme hydrogel composite material (GOD@PNI-co-AA-co-Py / MWCNTs). Referring to the method of Example 6, a carbon fiber electrode modified with a carbon nanotube-carrying enzyme hydrogel composite material was obtained. The effect on the enzyme catalytic activity was investigated.
[0083] The results are as follows Figure 7 As shown, the oxidation peak current increases with the increase of the multi-walled carbon nanotube content; when the mass ratio of enzyme-loaded hydrogel to multi-walled carbon nanotubes is 4:3, the oxidation peak current is the largest; as the carbon nanotube content continues to increase, the oxidation peak current decreases. Therefore, the preferred mass ratio of enzyme-loaded hydrogel to multi-walled carbon nanotubes is 4:3.
[0084] Example 9 Effect of Enzyme Loading Amount of Gel on Catalytic Activity
[0085] Enzyme-loaded hydrogels with different enzyme loading amounts were prepared by referring to the method of Example 3. Carbon fiber electrodes coated with carbon nanotube-enzyme-loaded hydrogel composite materials were prepared by referring to Examples 4 and 6, the molar ratio of N-isopropylacrylamide, acrylic acid, and 1-pyrene methacrylate was 15:2:2, and the mass ratio of enzyme-loaded hydrogel to multi-walled carbon nanotubes was 4:3. The effect on the enzyme catalytic activity was investigated.
[0086] like Figure 8 As shown, the results show that the oxidation peak current increases with the increase of the content of glucose oxidase in the hydrogel, and when the glucose oxidase and the hydrogel are prepared at a mass ratio of 1:1 to prepare the enzyme-loaded hydrogel, the oxidation peak current reaches the maximum value. Therefore, it is preferred that the glucose oxidase and the hydrogel are prepared at a mass ratio of 1:1 to prepare the enzyme-loaded hydrogel.
[0087] Example 10: Using electrochemical technology to explore the reversible detection of glucose molecules
[0088] The catalytic activity of the multi-enzyme cascade reaction is closely related to the distance between enzymes. Therefore, in order to further demonstrate the strategy of using near-infrared light to regulate the catalytic activity of enzymes, this example uses the glucose oxidase-horseradish peroxidase dual enzyme system as a model for the controllable analysis of glucose molecules. The working principle of the enzyme cascade reaction is as follows: in the presence of glucose molecules, glucose oxidase catalyzes glucose to produce gluconic acid and hydrogen peroxide; horseradish peroxidase further catalyzes the reduction of hydrogen peroxide to water, while accelerating the oxidation of the electron mediator methylene blue, thereby generating an electrochemical signal.
[0089] The enzyme-loaded hydrogel containing glucose oxidase and horseradish peroxidase was prepared by referring to the method of Example 3. The PNI-co-AA-co-Py hydrogel (2 mg) prepared in Example 1 was suspended in a buffer (5 mL) containing 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC, 4 mg). At 4°C, the EDC-activated hydrogel was mixed with glucose oxidase (GOD, 1 mg), horseradish peroxidase (HRP, 1 mg), and methylene blue (0.04 mmol / L) for 10 hours. After the reaction was completed, it was purified to prepare an enzyme-loaded hydrogel (GOD-HRP@PNI-co-AA-co-Py). A carbon fiber electrode coated with a carbon nanotube-enzyme-loaded hydrogel composite material was prepared by referring to Examples 4 and 6. The molar ratio of N-isopropylacrylamide, acrylic acid, and 1-pyrene methylacrylate was 15:2:2, and the mass ratio of the enzyme-loaded hydrogel to the multi-walled carbon nanotube was 4:3. The effect on the catalytic activity of the enzyme was investigated.
[0090] like Fig. 9As shown in A, in the presence of glucose molecules, the electrochemical response is weak when there is no near-infrared light irradiation. However, after near-infrared light irradiation, the electrochemical signal is significantly enhanced, indicating that an enzyme cascade catalytic reaction has occurred. This is mainly because under near-infrared light irradiation, the hydrogel shrinks and the distance between enzymes is shortened, thereby shortening the diffusion path of the substrate and further enhancing the electrochemical signal. In addition, the distance between the composite material and the electrode surface is shortened, which is conducive to the transfer of electrons to the electrode interface. Fig. 9 As shown in B, as the glucose concentration increases (0, 1.0, 2.0, 3.0, 4.0, 5.0 and 6.0 mM), the electrochemical signal gradually increases. The above results prove that the composite material modified electrode can be used for controllable analysis of biomolecules using near-infrared light as a control element.
[0091] Example 11 Application of the enzyme-based electrochemical biosensor of the present invention to controllable detection of glucose molecules in mouse brain
[0092] First, the mouse was fixed on a brain stereotaxic apparatus, and then the carbon fiber electrode, silver / silver chloride reference electrode, and platinum counter electrode prepared in Example 10 were implanted into the mouse brain. A 1064 nm laser was used as the light source at 1.0 W / cm 2 The electrochemical response of the modified electrode to glucose molecules was investigated before and after near-infrared light irradiation.
[0093] like Fig.10 As shown in the figure, the electrochemical response is weak without near-infrared light irradiation. After near-infrared light irradiation, the electrochemical signal is significantly enhanced. This proves that near-infrared light can be used as an external control element to achieve controllable detection of glucose in the mouse brain.
Claims
1. A temperature-responsive hydrogel, characterized in that The hydrogel is formed by a polymerization reaction of copolymer monomers: N-isopropylacrylamide, 1-pyrene methacrylate and acrylic acid and a crosslinking agent initiated by a free radical initiator.
2. The temperature-responsive hydrogel according to claim 1, characterized in that The molar ratio of N-isopropylacrylamide, 1-pyrene methacrylate and acrylic acid is 13-16:1-4:1-4.
3. The temperature-responsive hydrogel according to claim 1, characterized in that The molar ratio of N-isopropylacrylamide, 1-pyrene methacrylate and acrylic acid is 15:2:
2.
4. The temperature-responsive hydrogel according to claim 1, characterized in that The cross-linking agent is selected from one or more of N,N-methylenebisacrylamide, ethylene glycol dimethacrylate, and polyethylene glycol diacrylate.
5. The temperature-responsive hydrogel according to claim 1, characterized in that The free radical initiator is selected from one or more of ammonium persulfate, potassium persulfate and azobisisobutyronitrile.
6. The temperature-responsive hydrogel according to claim 1, characterized in that The molar ratio of comonomer, crosslinker and free radical initiator is 19:0.75:0.
45.
7. The temperature-responsive hydrogel according to claim 1, characterized in that The hydrogel is prepared by the following method: N-isopropyl acrylamide, 1-pyrene methyl acrylate and acrylic acid are dissolved in water, N,N-methylenebisacrylamide and sodium dodecyl sulfate are added in sequence, the mixed solution is heated under a nitrogen environment, ammonium persulfate is added to initiate a polymerization reaction, the reaction is cooled to room temperature after the reaction is completed, and unreacted monomers are removed by dialysis to obtain a hydrogel.
8. An enzyme-loaded hydrogel, characterized in that The temperature-responsive hydrogel according to any one of claims 1 to 7 is loaded with biological enzymes by one or more of the following methods: physical adsorption, chemical cross-linking, and covalent bonding.
9. The enzyme-loaded hydrogel according to claim 8, characterized in that The biological enzyme is selected from glucose oxidase and / or horseradish peroxidase.
10. The enzyme-loaded hydrogel according to claim 8, characterized in that Use cross-linkers to connect bioenzyme molecules to the temperature-responsive hydrogel.
11. The enzyme-loaded hydrogel according to claim 10, characterized in that The cross-linking agent is selected from 1-ethyl-(3-dimethylaminopropyl)carbodiimide and / or N-hydroxysuccinimide.
12. The enzyme-loaded hydrogel according to claim 10, characterized in that The mass ratio of the biological enzyme to the temperature-responsive hydrogel is 0.2-1.4:
1.
13. A carbon nanotube-enzyme-loaded hydrogel composite material, characterized in that The enzyme-loaded hydrogel doped with carbon nanotubes as described in claims 8-12.
14. The carbon nanotube-enzyme-loaded hydrogel composite material according to claim 13, characterized in that The carbon nanotubes are multi-walled carbon nanotubes.
15. The carbon nanotube-enzyme-loaded hydrogel composite material according to claim 13, characterized in that The mass ratio of carbon nanotubes to enzyme-loaded hydrogel is 0.6-4.2:
4.
16. Use of the temperature-responsive hydrogel according to any one of claims 1 to 7, the enzyme-loaded hydrogel according to claims 8 to 12, or the carbon nanotube-enzyme-loaded hydrogel composite material according to claims 13 to 15 in the preparation of an enzyme-based electrochemical biosensor.
17. The use according to claim 16, characterized in that The temperature-responsive hydrogel has a lower critical solution temperature higher than the physiological temperature of 37° C. It undergoes reversible swelling-contraction changes regulated by temperature or light to dynamically regulate the catalytic activity of the enzyme.
18. The use according to claim 17, characterized in that The carbon nanotube-enzyme-loaded hydrogel described in claims 13-15 undergoes reversible swelling-contraction changes under the control of near-infrared light to dynamically control the catalytic activity of the biological enzyme.
19. The use according to claim 18, characterized in that The carbon nanotube-enzyme hydrogel is exposed to near-infrared light with an excitation wavelength of 700-1700 nm and a power of 0.2-2.0 W / cm 2 , illumination time 0.1-5min.
20. A near-infrared light-controlled enzyme-based electrochemical biosensor, characterized in that The surface of the carbon electrode of the biosensor is coated with the enzyme-loaded hydrogel according to claims 8-12 or the carbon nanotube-enzyme-loaded hydrogel composite material according to claims 13-15.
Citation Information
Patent Citations
Novel non-phospholipid liposomes modified with a PH and temperature sensitive copolymer
CA2254554A1
Preparation method of fluorescent hydrogel, multi-dimensional information storage system and multi-dimensional information storage method
CN110903495A
Temperature, pH and light triple responsive microgel, preparation method and application of microgel in preparation of in-vitro drug controlled release drug
CN117003965A
Temperature sensing platform using fluorescent block copolymer combined with fret acceptor
KR1020150047316A
Carbon nanotube composite, semiconductor device and method for producing the same, and sensor using the same (as amended)
US20170263874A1